Developing the Framework for a Green Constitution: Strengthening Environmental Protection Initiatives in Indonesia - Hakim Rianta, Muhammad; Imron, Pradnya Kayla Ali; Danjuma, Ibrahim (The Indonesian Journal of International Clinical Legal Education, 2023)
The current global environmental crisis occurs due to various factors, such as failed policies, destructive technologies, and lack of political commitment. To address these issues, the green constitution approach has emerged as an effective solution. However, Indonesia has not fully implemented the concept of a green constitution. This research uses a normative legal research method with comparative, conceptual, and statutory approaches. Data is obtained from a literature study of national and international regulations, books, articles, and scientific journals. Through a comparative study with Ecuador and France, the results show that Indonesia has the potential to integrate environmental principles that have been integrated into the constitutions of these countries. Ecuador, often referred to as "The Real Green Constitution," explicitly recognizes the rights of nature and regulates preventive measures against environmental damage. In France, the Environmental Charter has been integrated into the constitution, affirming the need for wise management of the environment and a balance between protection and utilization of natural resources. Indonesia can learn from these two countries in applying the concept of a green constitution and integrating environmental principles into its constitution in order to strengthen environmental protection, promote sustainable development, and help address the impacts of climate change. The resulting recommendation is an amendment to the constitution to further incorporate environmental principles as part of the main elements in the constitution.